Influence of fuel properties on operational range and combustion characteristics of premixed diesel combustion with high volatility fuel. (August 2014) - Xiong, Qian; Inaba, Kazuki; Li, Tie; Shibata, Gen; Ogawa, Hideyuki
The effects of fuel properties including ignitability, volatility, and compositions on operational range and combustion characteristics of premixed diesel combustion with various high volatility model fuels and an ordinary diesel fuel were examined in a direct injection diesel engine. The indicated mean effective pressure was limited by knocking with high-intake oxygen concentrations and by unstable combustion or significant increases in CO and total hydrocarbon emissions with low-intake oxygen concentrations regardless of fuels. The fuel volatility has little effect on the combustion characteristics and the stable operational range in premixed diesel combustion. With increasing octane number, the combustion phasing is retarded, and higher intake oxygen concentrations can be employed within the tolerance limits of rapid combustion, expanding the stable premixed diesel combustion indicated mean effective pressure range. The operational range of premixed diesel combustion with normal heptane and toluene blend fuels shifts to higher intake oxygen concentrations when compared with primary reference fuels with the same research octane numbers, showing lower ignition characteristics than primary reference fuel. The silent, low-NOx, and smokeless operation with high thermal efficiency was possible with both primary reference fuel and normal heptane and toluene blend fuel when the intake oxygen concentration is optimized corresponding to indicated mean effective pressure.